Negative composite electrode of lithium ion battery, preparation of negative composite electrode and lithium ion battery

By designing a negative electrode composite electrode structure including a current collector, a first active material layer, a bonding layer and a second active material layer, the problems of large torsion, high rebound rate and poor bonding performance under high compaction density of lithium-ion battery negative electrode sheets are solved, and strong lithium ion transmission capability and excellent cycling stability are achieved.

CN119517933AActive Publication Date: 2025-02-25EVE POWER CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411640018.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The negative electrode sheets of existing lithium-ion batteries have problems such as large tortuousness, high rebound rate or poor bonding performance under high compaction density, resulting in insufficient kinetic performance, prone to lithium extraction or coating separation, affecting circulation performance.

Method used

The negative electrode composite electrode structure consisting of a current collector, a first active material layer, an adhesive layer and a second active material layer are adopted. The first active material layer contains a high conductivity long-range conductive agent, the adhesive layer contains a lithium conduction reinforcement material, and the second active material layer contains an oil-absorbing conductive agent. The design of these layers enhances the adhesion force and lithium ion transmission ability, and reduces the torsionality and rebound rate.

Benefits of technology

Under high compaction density, the negative electrode sheet has a small tortuousness, strong lithium ion transmission capacity, low rebound rate and good bonding performance of each layer, which improves the reaction kinetics performance, reduces the risk of separation of lithium-ion and coating, and significantly improves the cycle stability of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517933A_ABST
    Figure CN119517933A_ABST
Patent Text Reader

Abstract

The invention provides a negative composite electrode of a lithium ion battery, preparation of the negative composite electrode and the lithium ion battery. The negative composite electrode comprises a current collector, and a first active material layer, a bonding layer and a second active material layer which are sequentially arranged on the surfaces of the two sides of the current collector in the direction away from the current collector; the first active substance layer is composed of a first main material, a long-range conductive agent and a first binder; the bonding layer is composed of a second bonding agent, a conductive agent and a lithium conduction reinforcing material; and the second active substance layer is composed of a second main material, an oil absorption conductive agent and a third binder. According to the composite negative electrode, the tortuosity of a negative plate is relatively small under high compaction density, the lithium ion transmission capability is relatively high, the rebound rate is relatively low, and the bonding performance between layers is relatively good; therefore, the negative electrode composite electrode has good reaction kinetics performance, the risk of lithium separation is low, and the risk of separation between the layers is low; therefore, the lithium ion battery prepared from the negative electrode composite electrode has excellent cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a negative composite electrode of a lithium ion battery, in particular to a negative composite electrode of a lithium ion battery and a preparation method thereof and a lithium ion battery. Background Art

[0002] With the development of lithium-ion batteries, the requirements for energy density are getting higher and higher. The energy density is often increased by increasing the compaction density. However, with the increase in compaction density, the path for lithium ions to embed and escape inside the pole piece will become longer, which will also lead to a decrease in the pores of the pole piece, difficulty in electrolyte infiltration, greater pole piece tortuosity, and increased lithium ion diffusion resistance.

[0003] Conventional single-layer coating will cause the above problems. Therefore, in the prior art, pore-forming agents are added to increase the porosity of the electrode sheet, and pores are formed inside the active material to buffer the volume change during the charge and discharge process. However, the pore-forming agent cannot form open pores efficiently, and the residual pore-forming agent affects the performance of the battery. In addition, in the prior art, double-layer coating is also used to change the ratio of the upper and lower slurry layers to make the electrode sheet have gradient pores, increase the wettability of the electrolyte, facilitate the insertion and extraction of lithium ions, and improve the dynamic performance of the electrode sheet. However, there may be a problem of insufficient adhesion between the upper and lower slurries, which affects the cycle performance of the battery.

[0004] CN116914148A discloses a negative electrode sheet and a preparation method thereof, and a lithium ion battery. The negative electrode sheet comprises a current collector, a first coating, a second coating, and a third coating which are stacked in sequence, wherein the first coating comprises a first graphite active material, wherein the D50 of the first graphite active material is 20 μm to 25 μm, and the BET is ≤1 m 2 / g; the second coating includes a silicon-based active material and a second graphite active material, the surface of the silicon-based active material is coated with sodium polyacrylate; the surface of the second graphite active material is coated with carbon, the D50 of the second graphite active material is 10μm to 15μm, and the BET is 1m 2 / g~1.5m 2 / g; the third coating layer includes a third graphite active material having a porosity of 35% to 40%.

[0005] CN113178543A discloses a negative electrode sheet and a lithium-ion battery, wherein the negative electrode sheet comprises a current collector, a first coating, a second coating and a third coating; a pole ear is provided on one side of the current collector, a first coating area and a second coating area are provided on at least one surface of the current collector, and the first coating area is arranged close to the pole ear; the first coating covers the first coating area, the second coating covers the second coating area, and the thickness of the first coating is greater than the thickness of the second coating; the third coating is provided on a side of the first coating away from the current collector and on a side of the second coating away from the current collector.

[0006] The negative electrode sheets of lithium ion batteries disclosed in the prior art all have certain defects, such as large tortuosity, high rebound rate or poor bonding performance of the negative electrode sheets under high compaction density, which leads to insufficient dynamics of the negative electrode sheets, easy lithium precipitation, or easy separation between coatings, resulting in poor cycle performance of the battery prepared with the negative electrode sheets in the prior art. Therefore, it is very important to develop and design a new type of negative composite electrode for lithium ion batteries and its preparation and lithium ion batteries. Summary of the invention

[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a negative composite electrode for a lithium ion battery, its preparation and a lithium ion battery. The negative composite electrode provided by the present invention has a small tortuosity of the negative electrode sheet under high compaction density, a strong lithium ion transmission capacity, a low rebound rate and good bonding performance between layers; therefore, the negative composite electrode has good reaction kinetics, a low risk of lithium precipitation and a low risk of separation between layers; therefore, the lithium ion battery prepared with the negative composite electrode has excellent cycle stability.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a negative composite electrode for a lithium ion battery, the negative composite electrode comprising a current collector, and a first active material layer, a bonding layer and a second active material layer sequentially arranged on both side surfaces of the current collector in a direction away from the current collector;

[0010] The first active material layer is composed of a first main material, a long-range conductive agent and a first binder;

[0011] The bonding layer is composed of a second bonding agent, a conductive agent and a lithium conduction enhancing material;

[0012] The second active material layer is composed of a second main material, an oil-absorbing conductive agent and a third binder.

[0013] The first active material layer in the negative composite electrode provided by the present invention includes a long-range conductive agent with high conductivity, which can reduce the amount of conductive agent while increasing the amount of binder, thereby enhancing the bonding force between the first active material layer and the current collector, and the bonding force between the first main material, and reducing the risk of separation between the first active material layer and the current collector, and between the first main material during the cycle; in the negative composite electrode, by inserting a bonding layer containing a lithium conductivity enhancing material between the first active material layer and the second active material layer, the lithium ion transmission capacity of the negative composite electrode can be enhanced and the tortuosity of the negative composite electrode can be reduced while enhancing the bonding force between the first active material layer and the second active material layer; the second active material layer in the negative composite electrode includes an oil-absorbing conductive agent, thereby enhancing the electrolyte retention capacity of the negative composite electrode, ensuring sufficient electrolyte in the middle and late stages of the cycle, thereby improving the cycle performance.

[0014] The negative electrode composite electrode provided by the present invention has a small tortuosity of the negative electrode sheet under high compaction density, a strong lithium ion transmission capacity, a low rebound rate and good bonding performance between layers; therefore, the negative electrode composite electrode has good reaction kinetics, a low risk of lithium precipitation, and a low risk of separation between layers; therefore, the lithium ion battery prepared with the negative electrode composite electrode has excellent cycle stability.

[0015] Preferably, the first main material includes any one of graphite, soft carbon, hard carbon or graphene, or a combination of at least two of them. Typical but non-limiting combinations include a combination of graphite and soft carbon, a combination of soft carbon and hard carbon, a combination of hard carbon and graphene, a combination of graphite, soft carbon and hard carbon, or a combination of graphite, soft carbon, hard carbon and graphene.

[0016] Preferably, the long-range conductive agent comprises carbon nanotubes and / or carbon nanofibers.

[0017] Preferably, the first binder includes any one of carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyvinyl alcohol (PVA) or sodium alginate (SA) or a combination of at least two thereof. Typical but non-limiting combinations include a combination of CMC and SBR, a combination of SBR and PAA, a combination of PAA and PVA, a combination of PVA and SA, or a combination of CMC, SBR and PAA.

[0018] Preferably, the mass ratio of the first main material, the long-range conductive agent and the first binder in the first active material layer is (92-99):(2-6):(0.5-1.5).

[0019] The long-range conductive agent in the first active material layer of the present invention has excellent conductive properties. Therefore, when the amount of the long-range conductive agent is not high, the first active material layer can still have a high conductivity. In addition, the content of the first binder in the first active material layer is relatively high, which enhances the bonding performance of the first active material layer, thereby improving the bonding force between the first active material layer and the current collector, and the bonding force between the first main materials in the first active material layer, reducing the risk of separation between the first active material layer and the current collector during the cycle, and also reducing the risk of separation between the first main materials in the first active material layer, thereby reducing the rebound rate of the first active material layer, and therefore also reducing the rebound rate of the negative composite electrode.

[0020] The mass ratio of the first main material to the long-range conductive agent in the first active material layer of the present invention is (92-99):(2-6), for example, it can be 92:2, 92:3, 92:5, 92:6, 93:2, 93:3, 93:5, 93:6, 95:2, 95:3, 95:5, 95:6, 99:2, 99:3, 99:5 or 99:6, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] The mass ratio of the long-range conductive agent to the first binder in the first active material layer of the present invention is (2-6):(0.5-1.5), for example, it can be 2:0.5, 2:1, 2:1.5, 3:0.5, 3:1, 3:1.5, 5:0.5, 5:1, 5:1.5, 6:0.5 or 6:1, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] Preferably, the second binder comprises a combination of at least two of lithiated polyacrylic acid (PAA-Li), lithium carboxymethyl cellulose (CMC-Li), SBR, CMC or PAA, typical but non-limiting combinations include a combination of PAA-Li and CMC-Li, a combination of SBR and CMC, a combination of CMC and PAA, or a combination of SBR, CMC and PAA; preferably a combination of PAA-Li and CMC-Li.

[0023] When the second binder in the bonding layer of the present invention includes PAA-Li, PAA-Li can improve the lithium ion conductivity of the bonding layer while ensuring the bonding strength; when the second binder in the bonding layer includes CMC-Li, CMC-Li can not only ensure the bonding strength but also play a dispersing role and improve the uniformity of the bonding layer.

[0024] Preferably, the conductive agent in the bonding layer includes a combination of at least two of conductive carbon black (SP), vapor grown carbon nanofibers (VGCF) or single-walled carbon nanotubes (SWCNT), typical but non-limiting combinations are a combination of SP and VGCF, a combination of SP and SWCNT, or a combination of SP, VGCF and SWCNT; preferably a combination of SP and VGCF.

[0025] Preferably, the lithium conductivity enhancing material comprises lithium carbonate.

[0026] The use of lithium carbonate as a lithium conduction enhancing material in the bonding layer of the present invention can improve the lithium conduction capacity of the bonding layer, thereby improving the lithium ion conduction capacity of the negative composite electrode.

[0027] Preferably, the mass ratio of the second binder, the conductive agent and the lithium conduction enhancing material in the bonding layer is (20-40):(30-70):(1-10).

[0028] The mass ratio of the second adhesive to the conductive agent in the adhesive layer of the present invention is (20-40):(30-70), for example, it can be 20:30, 20:37, 20:47, 20:57, 20:67, 20:70, 27:30, 27:37, 27:47, 27:57, 27:67, 27:70, 37:30, 37:37, 37:47, 37:57, 37:67, 37:70, 40:30, 40:37, 40:47, 40:57, 40:67 or 40:70, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] The mass ratio of the conductive agent to the lithium conduction enhancing material in the bonding layer of the present invention is (30-70):(1-10), for example, it can be 30:1, 30:3, 30:7, 30:10, 30:1, 37:3, 37:7, 37:10, 47:1, 47:3, 47:7, 47:10, 57:1, 57:3, 57:7, 57:10, 67:1, 67:3, 67:7, 67:10, 70:1, 70:3 or 70:10, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] Preferably, the second main material includes any one of graphite, soft carbon, hard carbon or graphene, or a combination of at least two of them. Typical but non-limiting combinations include a combination of graphite and soft carbon, a combination of soft carbon and hard carbon, a combination of hard carbon and graphene, a combination of graphite, soft carbon and hard carbon, or a combination of graphite, soft carbon, hard carbon and graphene.

[0031] Preferably, the oil absorption value of the oil-absorbing conductive agent is ≥280mL / 100g, for example, it can be 280mL / 100g, 282mL / 100g, 284mL / 100g, 286mL / 100g, 288mL / 100g, 290mL / 100g, 293mL / 100g, 295mL / 100g, 297mL / 100g, 300mL / 100g, 305mL / 100g, 310mL / 100g, 315mL / 100g, 320mL / 100g, 330mL / 100g or 350mL / 100g, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0032] Preferably, the oil-absorbing conductive agent includes SP.

[0033] Preferably, the third binder includes any one of CMC, SBR, PAA, PVA or sodium alginate or a combination of at least two thereof. Typical but non-limiting combinations include a combination of CMC and SBR, a combination of PAA and PVA, a combination of PVA and sodium alginate, a combination of CMC, SBR and PAA, or a combination of CMC, SBR, PAA and PVA.

[0034] Preferably, the mass ratio of the second main material, the oil-absorbing conductive agent and the third binder in the second active material layer is (92-99):(0.5-3):(2.5-5).

[0035] The mass ratio of the second main material to the oil-absorbing conductive agent in the second active material layer of the present invention is (92-99):(0.5-3), for example, it can be 92:0.5, 93:0.5, 95:0.5, 97:0.5, 99:0.5, 92:1.3, 93:1.3, 95:1.3, 97:1.3, 99:1.3, 92:2.3, 93:2.3, 95:2.3, 97:2.3, 99:2.3, 92:3, 97:3 or 99:3, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0036] The mass ratio of the oil-absorbing conductive agent to the third binder in the second active material layer of the present invention is (0.5-3):(2.5-5), for example, it can be 0.5:2.5, 1.3:2.5, 1.7:2.5, 2.3:2.5, 2.7:2.5, 0.5:3.3, 1.3:3.3, 1.7:3.3, 2.3:3.3, 2.7:3.3, 0.5:4.3, 1.3:4.3, 1.7:4.3, 2.3:4.3, 2.7:4.3, 1.3:5, 1.7:5, 2.3:5 or 2.7:5, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] Preferably, the thickness of the first active material layer is 15 to 140 μm, for example, it can be 15 μm, 25 μm, 35 μm, 45 μm, 55 μm, 65 μm, 75 μm, 85 μm, 95 μm, 100 μm, 110 μm, 120 μm, 130 μm or 140 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] Preferably, the thickness of the bonding layer is 1 to 10 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 1 to 5 μm.

[0039] Preferably, the thickness of the second active material layer is 15 to 140 μm, for example, it can be 15 μm, 25 μm, 35 μm, 45 μm, 55 μm, 65 μm, 75 μm, 85 μm, 95 μm, 100 μm, 110 μm, 120 μm, 130 μm or 140 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] Preferably, the compaction density of the negative composite electrode is 1.35-1.80 g / cm 3 , for example, it can be 1.35 g / cm 3 , 1.4g / cm 3 , 1.45g / cm 3 , 1.5g / cm 3 , 1.55g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 , 1.75g / cm 3 or 1.8 g / cm 3 , but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] In a second aspect, the present invention provides a method for preparing the negative composite electrode according to the first aspect, the preparation method comprising:

[0042] A first slurry comprising a first main material, a long-range conductive agent and a first binder is prepared; a second slurry comprising a second binder, a conductive agent and lithium carbonate is prepared; a third slurry comprising a second main material, SP and a third binder is prepared; and the first slurry, the second slurry and the third slurry are used as raw materials to prepare a first coating, a second coating and a third coating on both sides of the current collector, and then cold pressed and compacted to obtain the negative electrode composite electrode sheet.

[0043] Preferably, the method of using the first slurry, the second slurry and the third slurry as raw materials to prepare the first coating layer, the second coating layer and the third coating layer on both sides of the current collector and stacking them in sequence in a direction away from the current collector surface comprises:

[0044] First, the first slurry is applied to the surface of the current collector to obtain a first coating after drying, and then the second slurry and the third slurry are applied to the surface of the first coating using a double-layer coating process to obtain a second coating and a third coating that are stacked in sequence in a direction away from the current collector.

[0045] After the first coating is prepared in the present invention, a double-layer coating method is adopted to bring the incompletely dried second slurry into contact with the first coating and the third slurry, thereby enhancing the bonding force between the second coating and the first coating and the third coating, and improving the structural stability of the negative composite electrode.

[0046] Preferably, the method of using the first slurry, the second slurry and the third slurry as raw materials to prepare the first coating layer, the second coating layer and the third coating layer on both sides of the current collector and stacking them in sequence in a direction away from the current collector surface comprises:

[0047] First, the first slurry is applied to the surface of the current collector, and the first coating is obtained after drying; then the second slurry is applied to the surface of the first coating, and the second coating is obtained after drying; then the third slurry is applied to the surface of the second coating, and the third coating is obtained after drying.

[0048] Preferably, the thickness of the first coating is 30 to 150 μm, for example, it can be 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] Preferably, the thickness of the second coating is 1 to 10 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, but is not limited to the listed values. Other unlisted values ​​within the numerical range are also applicable, preferably 1 to 5 μm.

[0050] Preferably, the thickness of the third coating is 30 to 150 μm, for example, it can be 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm or 150 μm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] In a second aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the negative composite electrode described in the first aspect.

[0052] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] (1) The first active material layer in the negative composite electrode provided by the present invention includes a long-range conductive agent with high conductivity, which can reduce the amount of the conductive agent while increasing the amount of the binder, thereby enhancing the bonding force between the first active material layer and the current collector, and the bonding force between the first main material, and reducing the risk of separation between the first active material layer and the current collector, and between the first main material during the cycle process;

[0055] (2) In the negative electrode composite electrode provided by the present invention, a bonding layer containing a lithium conductivity enhancing material is inserted between the first active material layer and the second active material layer, thereby enhancing the bonding force between the first active material layer and the second active material layer, improving the lithium ion transmission capacity of the negative electrode composite electrode and reducing the tortuosity of the negative electrode composite electrode;

[0056] (3) The second active material layer in the negative composite electrode provided by the present invention includes an oil-absorbing conductive agent, thereby improving the electrolyte retention capacity of the negative composite electrode, ensuring sufficient electrolyte in the middle and late stages of the cycle, thereby improving the cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0057] Figure 1 It is a schematic diagram of the structure of the negative composite electrode of the lithium ion battery provided in Examples 1 to 13 of the present invention.

[0058] Among them, 1 is current collector; 2 is first active material layer; 3 is bonding layer; 4 is second active material layer. DETAILED DESCRIPTION

[0059] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0060] Example 1

[0061] This embodiment provides a negative composite electrode for a lithium-ion battery, such as Figure 1 As shown, the compaction density of the negative composite electrode is 1.55 g / cm 3 The negative composite electrode comprises a current collector 1 with a thickness of 6 μm, and on both sides of the current collector 1, a first active material layer 2 with a thickness of 45 μm, a bonding layer 3 with a thickness of 2 μm, and a second active material layer 4 with a thickness of 45 μm are sequentially arranged in a direction away from the current collector 1;

[0062] The first active material layer 2 is composed of graphite in a mass ratio of 95:4:1, a long-range conductive agent (VGCF and SWCNT in a mass ratio of 1:1) and a first binder (CMC, SBR and PAA in a mass ratio of 1:1:3);

[0063] The bonding layer 3 is composed of a second bonding agent (PAA-Li and CMC-Li in a mass ratio of 30:68:2) and a conductive agent (SP and SWCNT in a mass ratio of 3:1, with an oil absorption value of SP of 290 mL / 100 g) and lithium carbonate;

[0064] The second active material layer 4 is composed of graphite in a mass ratio of 95:2.5:2.5, SP with an oil absorption value of 290 mL / 100 g, and a third binder (CMC, SBR, and PAA in a mass ratio of 1:1:3).

[0065] The preparation method of the negative composite electrode is:

[0066] A first slurry comprising graphite, a long-range conductive agent and a first binder is prepared; a second slurry comprising a second binder, a conductive agent and lithium carbonate is prepared; a third slurry comprising graphite, SP and a third binder is prepared; the first slurry is first applied to the surface of the current collector 1, and after drying, a first coating layer having a thickness of 70 μm is obtained, and then the second slurry and the third slurry are applied to the surface of the first coating layer by a double-layer coating process, so as to obtain a second coating layer having a thickness of 3 μm and a third coating layer having a thickness of 70 μm, which are sequentially stacked in a direction away from the current collector 1, and then cold pressed to obtain the negative electrode composite electrode sheet.

[0067] Example 2

[0068] This embodiment provides a negative composite electrode for a lithium ion battery, wherein the compaction density of the negative composite electrode is 1.55 g / cm 3 The negative composite electrode comprises a current collector 1 with a thickness of 6 μm, and on both sides of the current collector 1, a first active material layer 2 with a thickness of 45 μm, a bonding layer 3 with a thickness of 2 μm, and a second active material layer 4 with a thickness of 45 μm are sequentially arranged in a direction away from the current collector 1;

[0069] The first active material layer 2 is composed of graphite with a mass ratio of 95:4:1, a long-range conductive agent (VGCF and SWCNT with a mass ratio of 1:1) and a first binder (CMC, SBR and PAA with a mass ratio of 1:2:3);

[0070] The bonding layer 3 is composed of a second bonding agent (PAA-Li and CMC-Li in a mass ratio of 3:1) with a mass ratio of 27:70:2, a conductive agent (SP and SWCNT in a mass ratio of 3:1, and the oil absorption value of SP is 290 mL / 100 g) and lithium carbonate;

[0071] The second active material layer 4 is composed of graphite in a mass ratio of 95:2.5:2.5, SP with an oil absorption value of 290 mL / 100 g, and a third binder (CMC, SBR, PAA in a mass ratio of 1:1:3).

[0072] The preparation method of the negative composite electrode is:

[0073] A first slurry comprising a first main material, a long-range conductive agent and a first binder is prepared; a second slurry comprising a second binder, a conductive agent and lithium carbonate is prepared; a third slurry comprising a second main material, SP and a third binder is prepared; the first slurry is first applied to the surface of the current collector 1, and a first coating with a thickness of 70 μm is obtained after drying; the second slurry is then applied to the surface of the first coating, and a second coating with a thickness of 3 μm is obtained after drying; the third slurry is then applied to the surface of the second coating, and a third coating with a thickness of 70 μm is obtained after drying, and then cold pressing is performed to obtain the negative electrode composite electrode sheet.

[0074] Example 3

[0075] This embodiment provides a negative composite electrode for a lithium ion battery, wherein the compaction density of the negative composite electrode is 1.55 g / cm 3The negative composite electrode comprises a current collector 1 with a thickness of 6 μm, and on both sides of the current collector 1, a first active material layer 2 with a thickness of 45 μm, a bonding layer 3 with a thickness of 2 μm, and a second active material layer 4 with a thickness of 45 μm are sequentially arranged in a direction away from the current collector 1;

[0076] The first active material layer 2 is composed of graphite with a mass ratio of 95:4:1, a long-range conductive agent (VGCF and SWCNT with a mass ratio of 1:1) and a first binder (CMC, SBR and PAA with a mass ratio of 1:2:3);

[0077] The bonding layer 3 is composed of a second bonding agent (PAA-Li and CMC-Li in a mass ratio of 32:66:2) and a conductive agent (SP and SWCNT in a mass ratio of 3:1, with the oil absorption value of SP being 290 mL / 100 g) and lithium carbonate;

[0078] The second active material layer 4 is composed of graphite in a mass ratio of 95:2.5:2.5, SP with an oil absorption value of 290 mL / 100 g, and a third binder (CMC, SBR, PAA in a mass ratio of 1:1:3).

[0079] The preparation method of the negative composite electrode is:

[0080] A first slurry comprising a first main material, a long-range conductive agent and a first binder is prepared; a second slurry comprising a second binder, a conductive agent and lithium carbonate is prepared; a third slurry comprising a second main material, SP and a third binder is prepared; the first slurry is first applied to the surface of the current collector 1, and after drying, a first coating layer with a thickness of 70 μm is obtained, and then a second slurry and a third slurry are applied to the surface of the first coating layer using a double-layer coating process, so as to obtain a second coating layer with a thickness of 3 μm and a third coating layer with a thickness of 70 μm, which are sequentially stacked in a direction away from the current collector 1, and then cold pressed to obtain the negative electrode composite electrode sheet.

[0081] Example 4

[0082] This embodiment provides a negative composite electrode for a lithium-ion battery, wherein the first active material layer 2 is 45 μm thick, the bonding layer 3 is 1.6 μm thick, and the second active material layer 4 is 45 μm thick, except that the thickness of the first active material layer 2 and the thickness of the bonding layer 3 are 1.6 μm and 1.6 μm, respectively, in a direction away from the current collector 1.

[0083] That is, in the preparation method of the negative composite electrode, the thickness of the first coating layer is 70 μm, the thickness of the second coating layer is 2.5 μm, and the thickness of the third coating layer is 70 μm, and the rest is the same as that of Example 1.

[0084] Example 5

[0085] This embodiment provides a negative composite electrode for a lithium-ion battery, wherein the first active material layer 2 is 45 μm thick, the bonding layer 3 is 2.3 μm thick, and the second active material layer 4 is 45 μm thick, except that the thickness of the first active material layer 2 is 45 μm, the thickness of the bonding layer 3 is 2.3 μm, and the thickness of the second active material layer 4 is 45 μm.

[0086] That is, in the preparation method of the negative composite electrode, the thickness of the first coating layer is 70 μm, the thickness of the second coating layer is 3.5 μm, and the thickness of the third coating layer is 70 μm, and the rest is the same as that of Example 1.

[0087] Example 6

[0088] This embodiment provides a negative composite electrode for a lithium-ion battery, wherein the first active material layer 2 is 52 μm thick, the bonding layer 3 is 2 μm thick, and the second active material layer 4 is 52 μm thick, except that the thickness of the first active material layer 2 is 52 μm, the thickness of the bonding layer 3 is 2 μm, and the thickness of the second active material layer 4 is 52 μm.

[0089] That is, in the preparation method of the negative composite electrode, the thickness of the first coating layer is 80 μm, the thickness of the second coating layer is 3 μm, and the thickness of the third coating layer is 80 μm, and the rest is the same as that of Example 1.

[0090] Example 7

[0091] This embodiment provides a negative composite electrode for a lithium ion battery, wherein the compaction density of the negative composite electrode is 1.35 g / cm 3 The negative composite electrode comprises a current collector 1 with a thickness of 6 μm, and on both sides of the current collector 1, a first active material layer 2 with a thickness of 111 μm, a bonding layer 3 with a thickness of 3.7 μm, and a second active material layer 4 with a thickness of 111 μm are sequentially arranged in a direction away from the current collector 1;

[0092] The first active material layer 2 is composed of graphene, long-range conductive agent (carbon nanotube) and first binder (PVA or sodium alginate in a mass ratio of 1:1) in a mass ratio of 92:6:1.5;

[0093] The bonding layer 3 is composed of a second bonding agent (PAA-Li and CMC-Li in a mass ratio of 3:1) with a mass ratio of 40:30:10, a conductive agent (SP and SWCNT in a mass ratio of 3:1) and lithium carbonate;

[0094] The second active material layer 4 is composed of graphene in a mass ratio of 99:0.5:2.5, SP with an oil absorption value of 300 mL / 100 g, and a third binder (CMC and SBR in a mass ratio of 1:1).

[0095] The preparation method of the negative composite electrode is:

[0096] A first slurry comprising graphene, a long-range conductive agent and a first binder is prepared; a second slurry comprising a second binder, a conductive agent and lithium carbonate is prepared; a third slurry comprising graphene, SP and a third binder is prepared; the first slurry is first applied to the surface of the current collector 1, and after drying, a first coating layer with a thickness of 150 μm is obtained, and then a second slurry and a third slurry are applied to the surface of the first coating layer by a double-layer coating process, so as to obtain a second coating layer with a thickness of 5 μm and a third coating layer with a thickness of 150 μm, which are sequentially stacked in a direction away from the current collector 1, and then cold pressed to obtain the negative electrode composite electrode sheet.

[0097] Example 8

[0098] This embodiment provides a negative composite electrode for a lithium ion battery, wherein the compaction density of the negative composite electrode is 1.80 g / cm 3 The negative composite electrode comprises a current collector 1 with a thickness of 6 μm, and on both sides of the current collector 1, a first active material layer 2 with a thickness of 17 μm, a bonding layer 3 with a thickness of 1 μm, and a second active material layer 4 with a thickness of 17 μm are sequentially arranged in a direction away from the current collector 1;

[0099] The first active material layer 2 is composed of hard carbon, long-range conductive agent (nanocarbon fiber) and first binder (SBR and PAA in a mass ratio of 1:1) in a mass ratio of 99:2:0.5;

[0100] The bonding layer 3 is composed of a second bonding agent (PAA-Li and CMC-Li in a mass ratio of 3:1) with a mass ratio of 20:70:1, a conductive agent (SP and SWCNT in a mass ratio of 3:1) and lithium carbonate;

[0101] The second active material layer 4 is composed of hard carbon in a mass ratio of 92:3:5, SP with an oil absorption value of 320 mL / 100 g, and a third binder (PAA, PVA, and sodium alginate in a mass ratio of 3:1:1).

[0102] The preparation method of the negative composite electrode is:

[0103] A first slurry comprising hard carbon, a long-range conductive agent and a first binder is prepared; a second slurry comprising a second binder, a conductive agent and lithium carbonate is prepared; a third slurry comprising hard carbon, SP and a third binder is prepared; the first slurry is first applied to the surface of the current collector 1, and a first coating with a thickness of 30 μm is obtained after drying; the second slurry is then applied to the surface of the first coating, and a second coating with a thickness of 1 μm is obtained after drying; the third slurry is then applied to the surface of the second coating, and a third coating with a thickness of 30 μm is obtained after drying, and then cold pressing is performed to obtain the negative electrode composite electrode sheet.

[0104] Example 9

[0105] This embodiment provides a negative composite electrode for a lithium ion battery, which is the same as that of Embodiment 1 except that the mass ratio of the long-range conductive agent to the first binder in the first active material layer 2 is 2:2.5.

[0106] Example 10

[0107] This embodiment provides a negative composite electrode for a lithium ion battery, which is the same as that of Embodiment 1 except that the mass ratio of the long-range conductive agent to the first binder in the first active material layer 2 is 6:0.3.

[0108] Embodiment 11

[0109] This embodiment provides a negative composite electrode for a lithium-ion battery, which is the same as that of Embodiment 1 except that the second binder in the bonding layer 3 is replaced with PAA of the same mass.

[0110] Example 12

[0111] This embodiment provides a negative composite electrode for a lithium-ion battery, which is the same as that of Embodiment 1 except that the second binder in the bonding layer 3 is replaced with CMC of the same mass.

[0112] Example 13

[0113] This embodiment provides a negative composite electrode for a lithium ion battery, which is the same as the embodiment 1 except that the conductive agent in the bonding layer 3 is replaced with SWCNT of the same mass.

[0114] Comparative Example 1

[0115] This comparative example provides a negative composite electrode for a lithium-ion battery, which is the same as Example 1 except that the bonding layer between the first active material layer and the second active material layer is omitted.

[0116] Comparative Example 2

[0117] This comparative example provides a negative composite electrode for a lithium ion battery, wherein the compaction density of the negative composite electrode is 1.55 g / cm 3 The negative composite electrode comprises a current collector with a thickness of 6 μm, and an active material layer with a thickness of 90 μm covering both sides of the current collector 1;

[0118] The active material layer is composed of graphite in a mass ratio of 95:3:2, a conductive agent (SP and VGCF in a mass ratio of 3:1, and the oil absorption value of SP is 290 mL / 100 g) and a binder (CMC, SBR and PAA in a mass ratio of 1:1:3).

[0119] The preparation method of the negative composite electrode is:

[0120] A slurry containing graphite, a conductive agent and a binder is prepared; the prepared slurry is coated on the surface of the current collector 1, and a coating with a thickness of 140 μm is obtained after drying, and then cold pressing is performed to obtain the negative electrode composite electrode sheet.

[0121] Comparative Example 3

[0122] This comparative example provides a negative composite electrode for a lithium ion battery, wherein the compaction density of the negative composite electrode is 1.55 g / cm 3 The negative composite electrode comprises a current collector with a thickness of 6 μm, and an active material layer with a thickness of 90 μm covering both sides of the current collector;

[0123] The active material layer is composed of graphite in a mass ratio of 95:3:2, a conductive agent (SP and VGCF in a mass ratio of 3:1, and the oil absorption value of SP is 200 mL / 100 g) and a binder (CMC, SBR and PAA in a mass ratio of 1:1:3).

[0124] The preparation method of the negative composite electrode is:

[0125] A slurry containing graphite, a conductive agent and a binder is prepared; the prepared slurry is coated on the surface of a current collector, and after drying, a coating with a thickness of 140 μm is obtained, and then cold pressing and compacting are performed to obtain the negative electrode composite pole piece.

[0126] Comparative Example 4

[0127] This comparative example provides a negative composite electrode for a lithium ion battery, which is the same as Example 1 except that the long-range conductive agent in the first active material layer is replaced with SP of the same mass.

[0128] Comparative Example 5

[0129] This comparative example provides a negative composite electrode for a lithium ion battery, which is the same as Example 1 except that the lithium carbonate in the bonding layer is omitted.

[0130] Comparative Example 6

[0131] This comparative example provides a negative composite electrode for a lithium ion battery, which is the same as Example 1 except that the SP with an oil absorption value of 290 mL / 100 g in the second active material layer is replaced by the SP with an oil absorption value of 240 mL / 100 g.

[0132] The negative composite electrodes provided in the above embodiments and comparative examples are used to assemble a lithium-ion battery: the negative composite electrodes provided in the above embodiments and comparative examples are subjected to slitting and die-cutting processes to prepare negative electrode sheets.

[0133] The obtained negative electrode sheet was tested for its tortuosity: the obtained negative electrode sheet was assembled into a symmetrical battery, and the EIS was tested using an electrochemical workstation, with the frequency range set to 100,000 Hz to 0.1 Hz and the amplitude set to 5 mV; the measured Nyquist diagram was fitted with an equivalent circuit to obtain the ionic impedance Rion; the tortuosity was calculated by the formula τ = RionAεκ / t, where Rion is the liquid phase transmission impedance of ions in the electrode pores, A is the electrode apparent area, ε is the electrode porosity, κ is the ionic conductivity of the electrolyte, and t is the total thickness of the two electrodes. The tortuosity of the negative electrode sheet obtained by the test is shown in Table 1.

[0134] The obtained negative electrode sheet was subjected to a peeling force test: 3 groups of negative electrode sheets were taken from each embodiment, and a 180° peeling test was performed using a CBH-1 mechanical testing machine. The rate was set to 200 mm / min, and the average value of the three measurements was taken as the electrode sheet peeling force. The obtained peeling force of the negative electrode sheet is shown in Table 1.

[0135] The obtained negative composite electrode was subjected to a 24h rebound rate test: the thickness of the negative composite electrode obtained after the cold pressing step was immediately measured with a micrometer, and the average value of 10 points was taken as the initial thickness. After being placed for 24 hours, the thickness was measured again with a micrometer, and the average value of 10 points was taken as the thickness after 24 hours. The 24h electrode rebound rate = thickness after 24 hours / initial thickness. The obtained 24h electrode rebound rate is shown in Table 1.

[0136] The obtained negative electrode composite electrode was subjected to a full-charge rebound rate test: the thickness of the negative electrode composite electrode obtained after the cold pressing and compaction step was immediately measured with a micrometer, and the average value of 10 points was taken as the initial thickness; a negative electrode sheet was prepared from the negative electrode composite electrode, and then a lithium-ion soft-pack battery was prepared using the negative electrode sheet, and then the lithium-ion soft-pack battery after the capacity was fully charged, and then disassembled, and the thickness of the electrode sheet after disassembly was measured with a micrometer, and the average value of 10 points was taken as the full electrode sheet thickness, and the full-charge rebound rate = full electrode sheet thickness / initial thickness. The obtained full-charge rebound rate is shown in Table 1.

[0137] The negative electrode sheet prepared from the negative electrode composite electrode is used as the negative electrode, lithium iron phosphate is used as the positive electrode, and 1M LiPF6 (EC:DEC:DMC=1:1:1, volume ratio) is used as the electrolyte, and the stacking, liquid injection, packaging and vacuum sealing processes are carried out to obtain a lithium-ion soft-pack battery; then the obtained lithium-ion soft-pack battery is subjected to a cycle stability test; the cycle stability test includes a cycle stability test at 25°C and a cycle stability test at 45°C.

[0138] Cycle stability test at 25°C: At 25°C, the lithium iron phosphate battery was subjected to a 1C / 1C cycle test with a voltage range of 2.5 to 3.65V. The capacity retention rate was calculated by dividing the capacity after 500 cycles by the initial capacity. The 25°C cycle capacity retention rate is shown in Table 2.

[0139] Cycle stability test at 45°C: At 45°C, the lithium iron phosphate battery was subjected to a 1C / 1C cycle test with a voltage range of 2.5 to 3.65V. The capacity retention rate was calculated by dividing the capacity after 500 cycles by the initial capacity. The 45°C cycle capacity retention rate is shown in Table 2.

[0140] Table 1

[0141]

[0142] Table 2

[0143]

[0144] From Table 1, we can get:

[0145] (1) The negative composite electrode of the lithium ion battery provided in Examples 1 to 8 of the present invention has a lower tortuosity, a stronger peeling force, and a smaller 24h rebound rate and a full-charge rebound rate. The lithium ion soft-pack battery prepared with the negative composite electrode exhibits a stronger cycle stability;

[0146] (2) By comparing Example 1 with Examples 9 and 10, it can be seen that the mass ratio of the long-range conductive agent to the first binder in the first active material layer 2 of the present invention affects the performance of the negative composite electrode and the lithium ion soft-pack battery; when the mass ratio of the long-range conductive agent to the first binder is (2-6): (0.5-1.5), it is conducive to obtaining a negative composite electrode and a lithium ion soft-pack battery with better performance. This is because the long-range conductive agent added in an appropriate amount forms a three-dimensional conductive network between the graphite particles, which promotes the transmission of electrons during the charge and discharge process, and the matching of the appropriate amount of binder enables the three-dimensional conductive network to withstand the expansion and contraction of the graphite particles during the charge and discharge process, and still maintains the integrity of the structure; if the long-range conductive agent is excessive, it is difficult to disperse, and agglomeration occurs and an effective conductive network cannot be formed; if it is too little, the conductive network is incomplete; if the binder is too little, the bonding force is weak, so the integrity of the conductive network is always guaranteed during the cycle process; if it is too much, the electrode sheet resistance is increased, which affects the transmission of electrons;

[0147] (3) By comparing Example 1 with Examples 11 and 12, it can be seen that the second binder in the bonding layer 3 of the present invention affects the performance of the negative electrode composite electrode and the lithium ion soft-pack battery; when the binder is a combination of PAA-Li and CMC-Li, it is beneficial to obtain a negative electrode composite electrode and a lithium ion soft-pack battery with better performance. This is because PAA-Li can improve the lithium ion conductivity of the bonding layer 3 while ensuring the bonding force, and CMC-Li can play a dispersing role while ensuring the bonding force, thereby improving the uniformity of the bonding layer 3;

[0148] (4) By comparing Example 1 with Example 13, it can be seen that the conductive agent in the bonding layer 3 of the present invention will affect the performance of the negative electrode composite electrode and the lithium ion soft-pack battery; when the conductive agent is a combination of SP and SWCNT, it is beneficial to obtain a negative electrode composite electrode and a lithium ion soft-pack battery with better performance. This is because the proportion of the adhesive in the bonding layer 3 is large, and a conductive agent SWCNT with a long tube diameter is required to form a conductive network between the first active layer 2 and the second active layer 3 to ensure smooth transmission of electrons; in addition, since the inner layer has the problem of difficult infiltration of the electrolyte, by adding SP with a high oil absorption value, the electrolyte in the bonding layer 3 is sufficient, so that the first active layer 2 is more easily infiltrated by the electrolyte, and SP has the ability to retain electrolyte, and can provide electrolyte to the first active layer in the later stage of the cycle, thereby improving the cycle performance;

[0149] (5) By comparing Example 1 with Comparative Examples 1 to 6, it can be seen that the first active material layer 2 in the negative composite electrode provided by the present invention includes a long-range conductive agent with high conductivity, which can reduce the amount of conductive agent while increasing the amount of binder, thereby enhancing the bonding force between the first active material layer 2 and the current collector 1, and the bonding force between the first main material, and reducing the risk of separation between the first active material layer 2 and the current collector 1, and between the first main material during the cycle; in the negative composite electrode, by inserting a bonding layer 3 containing a lithium conductivity enhancing material between the first active material layer 2 and the second active material layer 4, the lithium ion transmission capacity of the negative composite electrode can be enhanced and the tortuosity of the negative composite electrode can be reduced; in the negative composite electrode, the second active material layer 4 includes an oil-absorbing conductive agent, thereby improving the electrolyte retention capacity of the negative composite electrode, ensuring sufficient electrolyte in the middle and late stages of the cycle, thereby improving the cycle performance.

[0150] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A negative composite electrode for a lithium-ion battery, characterized in that: The negative composite electrode comprises a current collector, and a first active material layer, a bonding layer and a second active material layer are sequentially arranged on both sides of the current collector in a direction away from the current collector; The first active material layer is composed of a first main material, a long-range conductive agent and a first binder; The bonding layer is composed of a second bonding agent, a conductive agent and a lithium conduction enhancing material; The second active material layer is composed of a second main material, an oil-absorbing conductive agent and a third binder.

2. The negative composite electrode according to claim 1, characterized in that: The first main material includes any one of graphite, soft carbon, hard carbon or graphene, or a combination of at least two thereof; Preferably, the long-range conductive agent comprises carbon nanotubes and / or carbon nanofibers; Preferably, the first binder includes any one of CMC, SBR, PAA, PVA or SA, or a combination of at least two thereof.

3. The negative composite electrode according to claim 1 or 2, characterized in that: The mass ratio of the first main material, the long-range conductive agent and the first binder in the first active material layer is (92-99):(2-6):(0.5-1.5).

4. The negative composite electrode according to any one of claims 1 to 3, characterized in that: The second binder comprises a combination of at least two of PAA-Li, CMC-Li, SBR, CMC or PAA, preferably a combination of PAA-Li and CMC-Li; Preferably, the conductive agent in the bonding layer includes a combination of at least two of SP, VGCF or SWCNT, preferably a combination of SP and VGCF; Preferably, the lithium conductivity enhancing material comprises lithium carbonate.

5. The negative composite electrode according to any one of claims 1 to 4, characterized in that: The mass ratio of the second binder, the conductive agent and the lithium conduction enhancing material in the bonding layer is (20-40):(30-70):(1-10).

6. The negative composite electrode according to any one of claims 1 to 5, characterized in that: The second main material includes any one of graphite, soft carbon, hard carbon or graphene, or a combination of at least two thereof; Preferably, the oil absorption value of the oil-absorbing conductive agent is ≥280mL / 100g; Preferably, the oil-absorbing conductive agent comprises SP; Preferably, the third binder includes any one of CMC, SBR, PAA, PVA or sodium alginate, or a combination of at least two thereof; Preferably, the mass ratio of the second main material, the oil-absorbing conductive agent and the third binder in the second active material layer is (92-99):(0.5-3):(2.5-5).

7. The negative composite electrode according to any one of claims 1 to 6, characterized in that: The thickness of the first active material layer is 15 to 140 μm; Preferably, the thickness of the adhesive layer is 1 to 10 μm, preferably 1 to 5 μm; Preferably, the thickness of the second active material layer is 15 to 140 μm; Preferably, the compaction density of the negative composite electrode is 1.35-1.80 g / cm 3 .

8. A method for preparing the negative composite electrode according to claim 1, characterized in that: The preparation method comprises: A first slurry comprising a first main material, a long-range conductive agent and a first binder is prepared; a second slurry comprising a second binder, a conductive agent and lithium carbonate is prepared; a third slurry comprising a second main material, SP and a third binder is prepared; and the first slurry, the second slurry and the third slurry are used as raw materials to prepare a first coating, a second coating and a third coating on both sides of the current collector, and then cold pressed and compacted to obtain the negative electrode composite electrode sheet.

9. The preparation method according to claim 8, characterized in that: The thickness of the first coating is 30 to 150 μm; Preferably, the thickness of the second coating is 1 to 10 μm, preferably 1 to 5 μm; Preferably, the thickness of the third coating layer is 30-150 μm.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative composite electrode according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Negative plate and lithium ion battery

    CN113178543A

  • Novel electrode slice and preparation method thereof, and solid-state battery equipped with the same

    CN109713218A

  • Negative pole piece and secondary battery comprising same

    CN114361457A

  • Negative plate, preparation method thereof and lithium ion battery

    CN115566136A

  • Multilayer coated pole piece, secondary battery, battery module, battery pack, and electric device

    CN115842092A